On the energy and pseudo-angle of Frenet vector fields in $R^n_v$ - Altin, A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In this paper, we compute the energy of a Frenet vector field and the pseudo-angle between Frenet vectors for a given non-null curve $C$ in semi-Euclidean space of signature $(n, v)$. It is shown that the energy and pseudo-angle can be expressed in terms of the curvature functions of $C$.